ANALISIS KECENDERUNGAN GEOPOLITIK INDONESIA DALAM ORGANISASI BRICS PADA PERSPEKTIF POLITIK LUAR NEGERI BEBAS AKTIF - Ragilia Dwi Pradita; Najwa Adhwa Ramadhani; Alifah Jasmine Kallista Remanu; Jerry Indrawan; Reja Reja (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
BRICS is an organization comprising a coalition of countries, namely Brazil, Russia, India, China, and South Africa. The countries in the BRICS coalition account for approximately 40% of the world’s population and hold a significant share of the global economy. Indonesia’s accession to BRICS could enhance its influence in regional dynamics and the political landscape and enable it to play a more prominent role in the global economy. However, this would inevitably clash with the concept of free and active foreign policy that Indonesia has long embraced. This study aims to analyze Indonesia’s free and active foreign policy concept, which continues to be implemented amidst the country’s growing involvement in the BRICS organization. The method employed in this study is a qualitative approach, which is understood as a means to uncover deeper meanings regarding social phenomena. The findings of this study indicate that Indonesia’s role within BRICS is viewed as a form of economic diplomacy and a short-term geopolitical strategy. Indonesia’s membership in BRICS also demonstrates an interest in expanding global influence in the economic sphere; however, by upholding the principle of a free and active foreign policy that remains non-aligned with any single nation, Indonesia maintains strategic flexibility and avoids excessive commitment to a single bloc. Therefore, Indonesia’s membership in BRICS can provide an opportunity to moderate the stance of more confrontational groups and facilitate dialogue between BRICS and Western nations.